2022
DOI: 10.31557/apjcp.2022.23.6.1967
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Avidin on Viability and Proliferation of Colorectal Cancer Cells HT-29

Abstract: Objective:The aim of this study was to analyze the effect of avidin treatment on cell viability, proliferation and cyclin D1 expression in colorectal cancer cells HT-29. Methods: Colorectal cancer cell line HT-29 incubated with 50, 100, 150, and 200 μg/mL of avidin concentration during 24, 48, and 72 hours, then the cell viability and proliferation were analyzed. Each avidin concentration was conducted together with HT-29 cell line without avidin treatment as a control group. The cell viability was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The new medium contained herb extracts at different concentrations. No extract was added in the control group (Dewi et al, 2022). To determine IC20, IC50, and IC80 values, cells were exposed to different concentrations of the water extract of P. spinosa for 24 and 48 hours (43.95, 87.89, 175, 351.56, 703.13, 1406.2, 2812.5, 5625, 11250, 22500 and 45000 µg/ml).…”
Section: Cell Culture and Applicationmentioning
confidence: 99%
“…The new medium contained herb extracts at different concentrations. No extract was added in the control group (Dewi et al, 2022). To determine IC20, IC50, and IC80 values, cells were exposed to different concentrations of the water extract of P. spinosa for 24 and 48 hours (43.95, 87.89, 175, 351.56, 703.13, 1406.2, 2812.5, 5625, 11250, 22500 and 45000 µg/ml).…”
Section: Cell Culture and Applicationmentioning
confidence: 99%
“…HT-29 cells possess the characteristics of mature intestinal cells, and thus can be used to study the anti-colon-cancer activities of substances. 22,23 Dewi et al investigated the anticolon cancer effect of avidin using colorectal cancer HT-29 cells and found that avidin can reduce the viability of the HT-29 colon cancer cell line and inhibit cell proliferation. 23 Therefore, in this study, PHPs were prepared via water extraction, ultra-high-pressure-, ultrasonic-and microwave-assisted water extraction.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Dewi et al investigated the anticolon cancer effect of avidin using colorectal cancer HT-29 cells and found that avidin can reduce the viability of the HT-29 colon cancer cell line and inhibit cell proliferation. 23 Therefore, in this study, PHPs were prepared via water extraction, ultra-high-pressure-, ultrasonic-and microwave-assisted water extraction. The effects of PHPs on the intestinal flora and SCFAs were determined during in vitro-simulated human intestinal flora fermentation.…”
Section: Introductionmentioning
confidence: 99%